Bedload entrainment dynamics in a partially channelized river with mixed bedload: A case study of the Drava River, Hungary. (31st March 2021) - Pirkhoffer, Ervin; Halmai, Ákos; Ficsor, Johanna; Gradwohl‐Valkay, Alexandra; Lóczy, Dénes; Nagy, Ádám; Liptay, Zoltán Árpád; Czigány, Szabolcs
Abstract: The morphodynamics of alluvial rivers is controlled by the mobilization of bed material. However, the details of mobilization of mixed‐texture bed materials at low flows, increasingly common due to climate change, are still unclear. The 161‐km‐long Hungarian alluvial reach of the Drava River, downstream of sections where flow characteristics have been heavily modified by human interference, was investigated in 2019. A monitoring campaign at cross‐sections, on average 5.55 km apart, was launched to study channel morphology, bedload entrainment dynamics with regard to texture. For the survey, a sonar, an ADCP and a Helley–Smith bedload sampler mounted on a double‐hull vessel was used. Our research pointed out an abrupt fining between river kms (hereafter: rkm) 175 and 170 (distance from the mouth), probably due to reduced armouring. The d 60 fraction was found to be finer than in 2003 and 2012 for the upstream stations of Botovo and Bélavár, and showed a good correspondence with the records of the Barcs and Drávaszabolcs stations. Temporal fining and higher entrainment rate are due to (a) changing climate of the catchment, that is, diminishing flow between the monitoring dates (2003, 2012 and 2019); (b) reduced armouring, (c) variability of cross‐sectional position of sampling points and (d) the different mesh size of the bedload samplers employed. Calculations of shear velocity, Reynolds and Shields numbers indicate more dynamic sediment motion than observed by previous studies. Our reach‐scale results may be relevant for the alluvial sections of other alpine and subalpine, partially channelized rivers of similar size, flow dynamics and mixed bedload.